If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 40a + 56b = 0 Solving 40a + 56b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-56b' to each side of the equation. 40a + 56b + -56b = 0 + -56b Combine like terms: 56b + -56b = 0 40a + 0 = 0 + -56b 40a = 0 + -56b Remove the zero: 40a = -56b Divide each side by '40'. a = -1.4b Simplifying a = -1.4b
| w^2-12w+17=0 | | 3(2g-5)=4g+13 | | r^2-5r^2+r=0 | | x+(x+12)=84 | | x-(x*.10)=12000 | | 12x-6=9y | | -t+10=-50+5t | | -t+19=-50+5t | | 8x-3=87-x | | 0.5t=-65 | | x+(x*.10)=12000 | | -5x=4 | | x*.10=12000 | | (3x+2y)(5x-4y)=0 | | -80+14x=-100-6x | | -93-9x=121-31x | | 360=x+35+90+90 | | 7x-9=x+39 | | G=3H+4K | | 7x-18+3x=17 | | 7x-110=2x-10 | | 65-3m=4m-5 | | 2x^2+20x-120=0 | | 107-7x=29x-19 | | -3(3p+6)-2(4-8p)-3(4+2p)=0 | | 15r-5=-10-10 | | 6x^2-48x=9 | | 5x+3+3y=18 | | x+10=-32+19 | | -8(2b+3)+(17b-3)=0 | | -y+2=16-8y | | 180=60+60+x-20 |